Eficiência nutricional de fósforo de clones de cafeeiro conilon - Martins, Lima Deleon (2011)
The knowledge about the efficiency of the plants in absorbing nutrients from the soil, and using them in growth and development is an important tool in the nutritional management of a culture. Thus the objective of this study was to evaluate the influence